Penerapan Habits Membaca Sebagai Rekontruksi Historical Peradaban Islam di Era Modern (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This article will discuss the application of reading results. Reading is the process of reviewing history to provide lessons for future developments. The aim of this research is to analyze the guidelines or systems used by the Abbasids which were able to make the Bani reach the golden peak. The method used in this research is a literature study which examines several articles and collects points related to the discussion. The results of this research are that the Abbasids used the Koran as a guide to guide their reign.